2017
DOI: 10.1177/009164711704500101
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Experiences of Humility Scale

Abstract: In three studies, we developed the Experiences of Humility Scale (EHS). In Study 1, we used exploratory factor analysis to determine the factor structure and to reduce items in a sample of undergraduates (N = 200). The EHS had four subscales: Other-orientation, Transcendence, Awareness of Selfishness, and Awareness of Egotism. Study 2 involved an experiment with a second sample of college students (N = 106) that provided initial evidence of construct validity. Participants assigned to a Meaning Condition (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
(67 reference statements)
0
21
0
4
Order By: Relevance
“…EHS, we reverse scored the "Selfishness" and "Egotism" subscale items, given they emphasize being "needy," "preoccupied," and so on (Davis et al, 2017). In the current study, Cronbach's ␣ was .79 for Week 1 and .77 for Week 4 for the entire sample.…”
Section: Homeworkmentioning
confidence: 83%
“…EHS, we reverse scored the "Selfishness" and "Egotism" subscale items, given they emphasize being "needy," "preoccupied," and so on (Davis et al, 2017). In the current study, Cronbach's ␣ was .79 for Week 1 and .77 for Week 4 for the entire sample.…”
Section: Homeworkmentioning
confidence: 83%
“…Sample items include "[I'm] more focused on others." "[I'm] part of something bigger than myself," "[I'm] 'small' in a good way," and "I've been too concerned with myself," and test-takers answer the 12 items in the context of "their most significant spiritual experience" (Davis et al, 2017). In the original validation study, the subscales demonstrated adequate internal consistency, and were linked to intrinsic religiousness and religious commitment (Davis et al, 2017).…”
Section: Experiences Of Humility Scale (Ehs)mentioning
confidence: 99%
“…The EHS is a 12-item measure of state humility, utilizing a 5-point Likert scale (1 ϭ strongly disagree to 5 ϭ strongly agree; Davis et al, 2017). The scale taps into several ingredients of humility, including four subscales: being "more focused on others" (Other-Orientation), "part of something bigger than myself" (Transcendence), "obsessed with my needs" (Selfishness), and "my perceptions of myself are overblown" (Egotism; Davis et al, 2017). Sample items include "[I'm] more focused on others."…”
Section: Experiences Of Humility Scale (Ehs)mentioning
confidence: 99%
“…Our views were informed by theirs in as much as we define humility as a personality judgment comprised of intrapersonal and interpersonal processes including: (a) accurate self‐view (intrapersonal); (b) willingness to admit limitations and mistakes (interpersonal); and (c) other‐focused orientation (interpersonal). Self‐reports are less than optimal in personality judgment in that the individual is both target and judge; however, social acceptance and interpersonal effectiveness are aided by an accurate perception of how one is viewed (Davis et al., ). Because self‐report can lead to reporter bias we controlled for socially desirable responding.…”
Section: Review Of Literaturementioning
confidence: 99%